2009
DOI: 10.1007/s12192-009-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

NGFI-B targets mitochondria and induces cardiomyocyte apoptosis in restraint-stressed rats by mediating energy metabolism disorder

Abstract: NGFI-B/Nur77/TR3, originally identified as an immediate-early gene rapidly induced by serum and growth factors, is a member of the steroid hormone nuclear receptor superfamily with no identified endogenous ligand. NGFI-B induces apoptosis in a number of cell lineages exposed to proapoptotic stimuli by directly targeting the mitochondria, inducing cytochrome c release. The present study was designed to determine the role of NGFI-B in cardiomyocytes of restraintstressed rats. The NGFI-B content was increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Mitochondria are vital for maintaining the physiological function of cardiomyocytes [44] [46] . Many stimuli can cause the mitochondrial MPTP to open [47] , with a subsequent series of cytological effects that includes a loss of mitochondrial transmembrane potentials, uncoupling of the respiratory chain, leakage of mitochondrial Ca 2+ , excess generation of ROS [48] , [49] , release of resident mitochondrial proteins such as the apoptosis initiating factor cytochrome c and release of a second mitochondria-derived activator of caspase [50] . These effects indicate that mitochondrial damage be a key step leading to myocardial death.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are vital for maintaining the physiological function of cardiomyocytes [44] [46] . Many stimuli can cause the mitochondrial MPTP to open [47] , with a subsequent series of cytological effects that includes a loss of mitochondrial transmembrane potentials, uncoupling of the respiratory chain, leakage of mitochondrial Ca 2+ , excess generation of ROS [48] , [49] , release of resident mitochondrial proteins such as the apoptosis initiating factor cytochrome c and release of a second mitochondria-derived activator of caspase [50] . These effects indicate that mitochondrial damage be a key step leading to myocardial death.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the stressful condition used in this dry eye model, an immobilized rat on a swing board in the presence of a continuous desiccated air blower, causes a decrease in tear secretion capacity accompanied an increased volume of secretory vesicles and loss of the intracellular cell structure, which indicates a dysfunction in the secretory system [7] . Exposure to stress is known to exacerbate the energy status of various organs, resulting in the loss of mitochondrial function [36] , [37] , [38] . In the present study, we showed a decrease in ATP levels and mitochondria content in the LG, in addition to lacrimal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Because restraint is considered to be a non-specific stressor, the animal model of restraint stress is often used to study the influence of stress on physiological functions and pathological processes. In a previous study, we observed cardiovascular function disruption and pathological alterations in the electrocardiograms of chronically restraint-stressed rats (Wang et al 2009). Cardiomyocyte damage is considered to be an important cellular basis for stress-induced cardiovascular injury and disease (Liu et al 2004).…”
Section: Discussionmentioning
confidence: 89%